Performance of unit trusts in Singapore - Lai, Chen-Yu (2008)
This research focuses on the unit trust industry in Singapore. Key aspects of the funds that are noteworthy to interested investors are investigated. In particular, emphasis is placed on the selections of fund managers, investment objectives and strategies, asset allocation decisions, as well as the much discussed CPF approved funds.